PROFIL AKTIVITAS PESERTA DIDIK PADA UNJUK KERJA BERBASIS PROYEK DALAM PEMBELAJARAN DARING MATERI SIFAT-SIFAT CAHAYA - Dita Hikmih Laily Sumantri (Lembaga Pengembangan Kinerja Dosen, 2022)
Signals, file size constraints when sending proof of student progress, and processing time, which may be delayed owing to other commitments, are all obstacles to integrating performance during online learning. This is due to differences in the implementation of online and offline performance. As a result, more study is needed to see how online learning activities improve project-based performance. The purpose of this study is to see how online learning habits influence project-based performance. The study included elementary school students. Data was acquired through observation and interviews because this is a qualitative research. In this investigation, observation and interviews were used as techniques. The data analysis strategies employed in this study included data reduction, data display, and data withdrawal/verification. Students' actions are good and in line with performance indicators, according to this study's findings. At SDN Menanggal 601, a project-based demonstration was held as part of this online learning using Google Meet and Microsoft Teams.